Enhancing dynamic impact performance and cushioning of EVA copolymer foams with thermoplastic elastomers - Chang, Boon Peng (2024)
This study examines the effect of thermoplastic elastomers (TPE) on the physical, mechanical, and dynamic impact properties of ethylene-vinyl acetate (EVA) copolymer foam using traditional chemical blowing process. The blending of EVA with TPE aims to improve both physical and dynamic impact cushioning to achieve optimal energyreturn EVA foam. Comparative analysis reveals that adding a 10–20 wt% fraction of propylene elastomer (POE) to EVA significantly reduces foam density while maintaining dynamic energy absorption and energy return. However, high POE content (30 wt%) leads to inferior mechanical and dynamic impact properties due to excessive softness. Blending EVA with terpolymer elastomer (PTW) enhances compression strength (∼16%), hardness (∼27%), and dynamic energy return (∼9%). EVA/POE/PTW hybrid blend foams display intermediate properties. The impact behaviors of foams vary between high and low dynamic impact loading rates. The presence of TPE enhances cushioning by absorbing impact forces through deformation, with EVA/PTW exhibiting remarkably improved rebound properties. Impact peak force decreases linearly with increasing PTW content. Foam morphology, including phase compatibility, cell size and density, plays a role in determining dynamic impact properties. Hard segmented TPE store more energy and quickly recover, resulting in a higher rebound effect as compared to soft segmented TPE. Incorporating TPE provides the ability to control the EVA foam's dynamic rebound, and impact cushioning, expanding its potential in sports-related applications.